Earthworms in grass lawns and native Atlantic Forest fragments at Embrapa Forestry, Colombo, Paraná state, Brazil - Dudas, Rafaela Tavares; Demetrio, Wilian C.; Roani, Rodrigo; Ferreira, Talita; Vanolli, Beatriz; Stiebler, Luiz P.p.m.; Souza, Mylla T.m.; Fontoura, Simone; Assis, Orlando; Ushiwata, Silvio; Moreira, Laiara; Ossowski, Maria E.; et al. (Zootaxa, 2025)
Earthworms are important soil biological indicators, but there is relatively little information on their communities in peri-urban soils and land uses in the subtropics. In the present paper, we describe earthworm occurrence and relationships with soil biological, chemical and physical attributes in grass lawns and native Atlantic Forest fragments in the Curitiba metropolitan area, using different sampling methods: quantitative handsorting, formalin extraction and qualitative sampling. Overall, 785 individuals, of six families and 12 species were found, four of which were native (Glossoscolex embrapaensis, Fimoscolex nivae, Urobenus brasiliensis and Ocnerodrilidae sp.), and eight exotic (Dichogaster bolaui, Dichogaster sp., Murchieona minuscula, Aporrectodea rosea, Amynthas gracilis, Amynthas morrisi, Metaphire californica and Pontoscolex corethrurus). Grass lawns had higher abundance (509 individuals) and diversity (Shannon-Wienner, Simpson and Pielou). Handsorting was the most effective sampling method (70% of all individuals). Exotic species predominanted in most areas (≥50% of individuals), indicating a higher degree of human disturbance. Biomass followed the same pattern as abundance, being higher in grass lawns. Multivariate analysis showed that chemical and biological soil attributes did not have a direct correlation with earthworm abundance, and that native forest fragments had higher acidity and C contents.